Case report: A rare case of recurrent right atrial mass dramatically disappeared after anticoagulation - Wang, Huarui; Zi, Jie; Li, Qiao; Sun, Yuanyuan; Zhu, Ling (Frontiers in Cardiovascular Medicine, 2022)
A young man repeatedly found a right atrial mass with severe wheezing and extreme dyspnea. His condition was critical and complicated. The process of correct diagnosis was full of twists and turns. Finally, he got better and was discharged from the hospital after anticoagulation therapy, which suggested that correct clinical thinking and decision are particularly important in the process of diagnosis and treatment.